Pengembangan Layanan Print Online Berbasis Website - Sahara, Siti; Hartawan, Miftaah Bagus; Zain, Zaldi Sultani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The development of information technology has revolutionized various aspects of life, including the printing industry. In response to these developments, a new alternative in document printing services, known as website-based online printing, has emerged. This service allows customers to place orders and print documents online through a unique website the printing company provides. This provides convenience and flexibility when accessing printing services. At the same time, printing shop owners can benefit from efficient order management and access to online sales data. The data for this study was collected through interviews and observation methods to obtain the necessary information for system development. The results of this research are expected to contribute to the advancement of online printing services that are more effective and efficient in today's digital era. By using website-based online print services, the printing industry can adapt to changes in customer demand and provide a good printing experience.